Far-Field Wireless Power Transfer Using GRIN Lens Metamaterial at GHz Frequency - Baghel, Amit K.; Kulkarni, Shashank S.; Nayak, Sisir K. (IEEE microwave and wireless components letters, 2019)
In this letter, the far-field wireless power transfer up to 6-m distance from the transmitting horn antenna (Tx) aperture using a new design gradient refractive index lens metamaterial (GRIN MM) is proposed for the first time, which increases the efficiency of power transfer. Double-sided-S-shaped GRIN MM unit cell dimensions are optimized for the operating frequency of 2.45 GHz. The D-dot sensor is placed at 6-m distance from the Tx aperture to measure the electric field without and with the proposed GRIN MM and hence the power density. The same amount of power is received experimentally without GRIN MM as obtained by the Friis transmission equation, thus validating the theoretical and experimental analysis. Experimentally, it is observed that due to the point directive beam obtained after passing through the GRIN MM array, 86% more power is received with it compared to without it, thus increasing the maximum theoretical power received.